The therapeutic potential of Apigenin in amyotrophic lateral sclerosis through ALDH1A2/Nrf2/ARE signaling - Huiting Liang; Xinhui Zhou; Jie Zhang; Wenyuan Xu; Yi Liu; Xinxin Wang; Yushu Hu; Renshi Xu; Xiaobing Li (Molecular Medicine)
Abstract Background Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease characterized by motor neuron loss leading to muscle weakness and atrophy. Apigenin (APG), known for its antioxidant properties, holds potential as a therapeutic compound in ALS. Methods We used the Tg(SOD1*G93A)1Gur/J transgenic mouse model of ALS to investigate the therapeutic effects of APG. Key measured included motor function via the ALSTDI score, molecular markers of oxidative stress (OS) and apoptosis in spinal cord tissues. Techniques used included pathological, Western blotting, flow cytometry, and qRT-PCR to assess the effect of ALDH1A2. Results APG treatment attenuated weight loss and improved motor function scores in ALS mice compared to untreated ALS models. Molecular analyses revealed a significant upregulation of ALDH1A2 in APG-treated groups, along with a reduction in markers of OS and apoptosis. In vitro studies in NSC34 cells further confirmed the protective effects of APG against SOD1*G93A mutation-induced cytotoxicity. In addition, suppression of ALDH1A2 by shRNA exacerbated disease markers that were ameliorated by APG treatment. Conclusions Our results suggest that APG attenuates the progression of ALS pathology by regulating OS and apoptosis through ALDH1A2. These results support further investigation of APG as a potential therapeutic agent for the treatment of ALS. Graphical Abstract